Pelvic stress fractures related to pregnancy - Reyna-Villasmil, Eduardo (2019)
Pelvic fractures, either traumatic or atraumatic, are relatively rare and should be considered in the differential diagnosis of low back pain in women. Pelvic stress fractures related to pregnancy are even rarer and poorly understood phenomena that pose diagnostic and therapeutic challenges. These fractures are caused by insufficiency or fatigue. Those that result from bone insufficiency occur when normal stress is placed upon bone with decreased mineralization and elastic resistance. Those caused by fatigue occur when abnormal forces are applied to normal bone. Pregnancy and lactation are risk factors for pelvic stress fracture. Most cases occur postpartum and few cases during the third trimester. Pelvic fracture should be considered in pregnant women with severe back pain of insidious onset before or after delivery, usually in the absence of trauma. Plain films of the pelvis are often inconclusive, while magnetic resonance is the best choice for diagnosis. Clinical presentation and radiographic findings can mimic other unrelated or overlapping conditions and may lead to underdiagnosis. The objective of this review is to summarize the available literature on pelvic stress fractures related to pregnancy.